Alternative Dispute Resolution In Cyber Dispute Resolution With Mediation Techniques - Jamillah, Jamillah; Maswandi, Maswandi (SASI, 2023)
Introduction: Law enforcement and protection for cyber cases is focused on the protection of cyber victims consisting of physical or psychological violence, retaliation, humiliation, and mistreatment of people who commit cyber crimes, the sophistication of the media makes people often involved with cyber crimes. Where the focus of this paper discusses alternative cyber dispute resolution.Purposes of the Research: The purpose of this study is to explain the concept of cyber dispute resolution by using mediation as an option.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: Cyber dispute resolution, cyber crimes that can be done anywhere, even with the sophistication of technology today is possible for a criminal to use equipment that allows difficult or even untraceable places about where the crime was committed so that the first step in alternative dispute resolution is using persuasive ways with mediation mechanisms and then further, improving the quality of law enforcement in, make the law as the basis in every action in order to create equality before the law and the rule of law.